Physical characteristics that predict functional performance in Division I college football players - Davis, D. S.; Barnette, B. J.; Kiger, J. T.; Mirasola, J. J.; Young, S. M. (The Journal of Strength and Conditioning Research, 2004)
Strength and conditioning professionals who work with collegiate football players focus much of their time and effort on developing programs to enhance athletic performance. Although there has been much speculation, there is little scientific evidence to suggest which combination of physical characteristics best predicts athletic performance in this population. The purpose of this investigation was to examine the relationship among 6 physical characteristics and 3 functional measures in college football players. Data were gathered on 46 NCAA Division I college football players. The 3 response variables were 36.6-m sprint, 18.3-m shuttle run, and vertical jump. The 6 regressor variables were height, weight, percentage of body fat, hamstring length, bench press, and hang clean. A stepwise multiple regression analysis was performed to screen for variables that predict physical performance. Regression analysis revealed clear prediction models for the 36.6-m sprint and 18.3-m shuttle run. The results of this investigation will help strength and conditioning specialists better understand the variables that predict athletic performance in Division I college football players.